PRIMARY DATA ON ICHTHYOFAUNA OF THE UPPER OF THE SYRDARYA RIVER (Scientific journal of the Fergana State University, 2024)
The article presents primary data based on the results of a study conducted on the composition of the ichthyofauna of the upper reaches of the Syrdarya River. The main part of the upper reaches of the Syrdarya River is located in the Fergana Valley. The species composition of fish living in this river has been studied by different researchers in different periods, and the latest work in it was carried out until the early 90s of the last century. In addition, in the last 50-60 years, the species composition of fish not only in the Syrdarya River but also in the entire Aral Basin has changed significantly. This change was caused mainly by anthropogenic factors. For example, some acclimatization work was carried out to enrich local water bodies with commercial fish species. Along with commercial species, random species also penetrated, the main part of which were non-commercial weed species. Based on the above, the study of the modern composition of the ichthyofauna in the upper reaches of the Syrdarya River is relevant. Preliminary data shows that the taxonomic status of the ichthyofauna of the upper reaches of the Syrdarya River currently consists of 6 orders, 11 families and 21 species. The article also provides a brief history of the study of the ichthyofauna of the Syrdarya River by various researchers.